A brief note concerning Hayek's non-standard conception of knowledge - Scott Scheall (Duke University, Center for the History of Political Economy (CHOPE), 2018)
Whatever F.A. Hayek meant by "knowledge" could not have been the justified true belief conception common in the Western intellectual tradition from at least the time of Plato onward. In this brief note, I aim to uncover and succinctly state Hayek's unique definition of knowledge.
Keywords: B2; B3; B4; B5; Y8; 330; F.A. Hayek; knowledge; economic coordination; justified true belief; methodology; market process